Atomic force microscopy analysis of biofilms formed on different plastics. (February 2015) - Hirai, N.; Mun, M. K.; Masuda, T.; Itoh, H.; Kanematsu, H.
Abstract : Biofilms formed on various plastics (vinyl chloride, silicone resin, Nylon 66, polycarbonate and polypropylene) have been investigated by atomic force microscopy (AFM) and optical microscopy (OM). A biofilm formation reactor (BFR) fabricated in our group was used for the biofilm formation on a laboratory scale. After biofilm formation for 4 days in BFR, the biofilm formed on silicone resin had a finely rugged surface, while that formed on vinyl chloride had only coarse ruggedness, suggesting that the surface texture of the biofilms depends on the kind of plastic on which they are formed. After biofilm formation for 4 weeks in BFR, both the root mean square roughness (Rq) and arithmetic mean roughness (Ra) were found to be dependent on the samples, in the order vinyl chloride>Nylon 66, polycarbonate>polypropylene.